Profil Sikap Ilmiah Peserta Didik Melalui Buku Ajar Elektronik IPA Berbasis Kearifan Lokal Pembuatan Garam Madura - Risky Nugraheni Purnamawati; Nurfina Aznam; Insih Wilujeng; Suyanta Suyanta; St Afifah (Jurnal Penelitian Pendidikan IPA, 2022)
Scientific attitude is very important for each individual student, especially in the learning process. The purpose of this study was to determine the profile of students' scientific attitudes by using an electronic science textbook based on local wisdom of Madura salt making. The research was conducted at SMP Negeri 2 Pademawu. This study uses a descriptive method with a quantitative approach. The population in this study was all class VII SMP Negeri 2 Pademawu. Samples were taken using a simple random sampling technique. Data was collected using an observation sheet for students' scientific attitudes consisting of 3 aspects, 9 indicators, and 10 statements and using interview techniques to add information about science learning. research results are included in the category of quite good. Therefore, these results still need to be improved so that they become very good by using models, methods, strategies, and textbooks that can improve students' scientific attitudes, one of the textbooks that can be used is electronic textbooks based on local wisdom.